Assets at marriage in rural Ethiopia - Fafchamps, Marcel; Quisumbing, Agnes R. (International Food Policy Research Institute, 2004)
This paper contributes to the economic analysis of marriage and the family by examining and analyzing the relative importance of potential determinants of assets brought to marriages in rural Ethiopia. One potential determinant is assortative matching, whereby the rich marry the rich and the poor marry the poor, generating a positive correlation between assets brought to marriage by both spouses. Another determinant explored is compensating parental transfers at marriage, whereby parents reduce assets transferred to their marrying children if their spouses bring more. The third determinant analyzed is parents' strategic behavior to improve the marriage-market ranking of their children by transferring more assets to them at the time of marriage. -- from Text